2012
DOI: 10.1021/jp2094388
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Conversion Properties of Dye-Sensitized Solar Cells Using Dye-Dispersing Titania

Abstract: The time-resolved fluorescence and photoelectrochemical properties of dyesensitized solar cells using crystalline titania electrodes coated with N3 dye-dispersing amorphous titania gel were investigated to clarify the influence of the dye−titania interaction and electron transfer on their photoelectric conversion performance. The photocurrent quantum efficiency of the electrodes was remarkably increased by a steam treatment due to the crystallization and densification of the amorphous titania layer compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 40 publications
3
48
1
Order By: Relevance
“…35−41 The dye molecules in such materials exhibit a more efficient absorption and electron injection because they are finely dispersed in the amorphous or nanosized crystalline matrices compared to the conventional dye-adsorbed materials. 37,39,40 In this study, the dye-dispersing titania electrodes were prepared from the dye-containing titanium alkoxide sols by a room temperature sol−gel process and steam treatment at 110°C.…”
Section: −11mentioning
confidence: 99%
“…35−41 The dye molecules in such materials exhibit a more efficient absorption and electron injection because they are finely dispersed in the amorphous or nanosized crystalline matrices compared to the conventional dye-adsorbed materials. 37,39,40 In this study, the dye-dispersing titania electrodes were prepared from the dye-containing titanium alkoxide sols by a room temperature sol−gel process and steam treatment at 110°C.…”
Section: −11mentioning
confidence: 99%
“…The shape of all the spectra was similar to the absorption spectra of titania exhibiting the absorption edge at around 400 nm. This indicated that the photocurrent was generated by the excited electrons in the titania [31,32]. Figure 4 shows the I-V curves of the electrode observed under the same conditions.…”
Section: Photocatalytic Reaction On the Electrodesmentioning
confidence: 82%
“…The compounds in such materials exhibit a more efficient light harvesting and fluorescence because they are finely dispersed in the amorphous or nanosized crystalline matrices compared to the conventional dye-adsorbing materials [20][21][22][23]. Therefore, it is expected that such films exhibit a higher function, stability, and performance in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…The organic dye-dispersing titania gel is suited for the dye-titania complex formation because the dye molecules with carbonyl and/or carboxyl groups are encapsulated in the narrow spaces of the gel [20][21][22][23][24][25][26]. The xanthene dye-dispersing titania gel was prepared without heating from a titanium alkoxide sol containing the dye molecules by the sol-gel method [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation